Analysis of The Influence of Electronic Word of Mouth, Brand Awareness and Digital Accessibility on Purchase Decision of Sayurbox Consumers - Sudirjo, Frans; Astuti, Ambar Kusuma; Parandy, La Mema; Kowey, Wylda Olivia; Transistari, Ralina (SEULANGA SYSTEM PUBLISHER, 2023)
Based on variables related to consumer behavior, the purpose of this study is to examine how brand awareness, electronic word-of-mouth (eWOM), and digital accessibility affect purchase decisions. Both quantitative and qualitative data are the kind of data that are employed. Both primary and secondary data sources are utilised. Customers of e-grocery who purchase fruit are sent a questionnaire via Google Form as part of the data collection process. The researcher came to the conclusion that there were 100 respondents in the sample. Both qualitative and quantitative analysis will be performed on the data collected from the questionnaire. In order to test the research concurrently, structural equation modeling (SEM) and partial least squares (PLS) analysis are utilized, with the smartPLS program. Drawing from the analysis and explanation presented above, the following deductions can be made: The behavior of consumers is not really impacted by brand awareness. Digital accessibility and electronic word-of-mouth (eWOM) have a genuine and substantial impact on e-grocery consumer behavior. It's probable that customer behavior is influenced by the lifestyle of internet buying. Purchase decisions are actually and significantly influenced by digital accessibility and brand awareness. Digital accessibility and electronic word-of-mouth have a genuine and substantial impact on customer behavior. Opinion leaders and reference groups may have an impact on customer behavior when it comes to emotional factors influencing purchase decisions.